Textbook Analysis of Pancasila and Civic Education and Curriculum in State Vocational High School 6 Palu - Jamaludin Jamaludin; Riska Tambidjonga; Juisda Elisabet; Isti Qumaira; Nurhadija Nurhadija; Nuralia Hamdan; Intan Triana; Sarwina Ayu Lestari; Umul Astifa; Nadila Yulianingsi; Parigul Parigul; Lisdayani Lisdayani; Gerhana Gerhana; Nur Azizah; Widya Astuti; Rini Wulandari; Shofia Nurun Alanur; Sumawati Sukmawati (CV. Rayyan Dwi Bharata, 2023)
This study focused on